Studies in the Medieval Atlantic
XV, 271 p.
Keywords: This collection of essays offers fresh analysis of topics in the exciting area of Atlantic World studies. Challenging standard assumptions, the essays advance the argument that the Atlantic Ocean was a region that encompassed ethnic and political boundaries, in which a sub-community shaped by culture and commerce arose.